Literary Space in Selected Youth Fiction by Branka Jurca (Preučevanje otroške in mladinske književnosti, 2025)
In 2024 we celebrate the 110th birth anniversary of Branka Jurca (died in 1999) who contributed over thirty books for children and youth to Slovenian literature. Her youth novel Ko zorijo jagode (1974) and the modern fairy tale Snežaki v vrtcu (1983) are still being reprinted. Her life was marked by three spaces: the Karst, where she was born at the outset World War I; the Styria, where she spent her childhood, youth and first working years as a teacher between the two wars; and Ljubljana, where she lived in her mature, adult years after the Second World War. Using the methodology of spatial literary studies, the paper investigates the reflection of real space in Jurca’s literature, especially in her autobiographical fiction Rodiš se samo enkrat (1972), the adventure stories Uhač in njegova druščina (1963) and Vohljači in prepovedane skrivnosti (1966) and the youth novel Ko zorijo jagode (1974).